2019
DOI: 10.20944/preprints201901.0213.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inorganic and Hybrid Perovskite Based Laser Devices : A Review

Abstract: Inorganic and organic – inorganic (hybrid) perovskite semiconductor materials have attracted the worldwide scientific attention and research effort as the new wonder material in optoelectronics. Their excellent physical and electronic properties have been exploited to boost the solar cells efficiency beyond 23% and captivate their potential as competitors to the dominant silicon solar cells technology. However, the fundamental principles in Physics dictate that an excellent material for photovoltaic applicatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Nanostructured lead halide perovskite materials have gained significant attention in the last few years mainly because of their potential for application in the field of electronics and photonics. There are several available reports demonstrating their implementation into light emitting diodes (LED) 1 3 , solid-state lasers 4 , solar cells 5 , photodetectors 6 and optical cooling systems 7 . Especially the photoluminescence quantum yields (PLQY) of up to 100% make these nanostructured perovskite materials very interesting 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured lead halide perovskite materials have gained significant attention in the last few years mainly because of their potential for application in the field of electronics and photonics. There are several available reports demonstrating their implementation into light emitting diodes (LED) 1 3 , solid-state lasers 4 , solar cells 5 , photodetectors 6 and optical cooling systems 7 . Especially the photoluminescence quantum yields (PLQY) of up to 100% make these nanostructured perovskite materials very interesting 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Some works examined new different excitonic properties of the 2D organicinorganic halide perovskite materials showing that this type of perovskite is very qualified to be used for the construction of the photonics devices [96][97][98] containing LEDs [99,100], photodetectors [101], transistors, and lasing applications [102]. Wang et al [103] provided a valuable research about the special characteristics of the long-lived exciton, trion, and biexciton cases in CdSe/CdTe colloidal QWs, proposing a novel model of light harvester with minimal energy losses.…”
Section: Excitons and Biexcitons In Two-dimensional Semiconductor Strmentioning
confidence: 99%
“…PNSs represent larger exciton binding energies and longer carrier decay times than those of bulk crystals. In addition to this, their narrow emission band makes them good candidates for LED [16] and laser [17]. Since Schmidt et al reported the synthesis of first colloidal PNS by a simple procedure under ambient conditions in 2014 [18], many research groups have started working on these materials.…”
Section: Introductionmentioning
confidence: 99%